2021
DOI: 10.3390/plants10061062
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Root Induction from Argan (Argania spinosa (L.) Skeels) Adventitious Shoots: Influence of Ammonium Nitrate, Auxins, Silver Nitrate and Putrescine, and Evaluation of Plantlet Acclimatization

Abstract: Argania spinosa (L.) Skeels is an endangered plant species endemic to Morocco. In recent years, attempts to develop in vitro regeneration systems for this species were made. However, rooting and acclimatization of in vitro plants have been a bottleneck for successful propagation. In the present study, the effects of different concentrations of auxins, putrescine, silver nitrate (AgNO3) and ammonium nitrate on the in vitro rooting of adventitious shoots of two argan genotypes “Mejji” and “R’zwa”, were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 56 publications
2
5
0
Order By: Relevance
“…This indicates that in order to ensure a high survival rate and good growth status of the transplanted plants, the nutrition and air permeability of the transplant substrate are indispensable. The present result is in agreement with the previous ndings observed in Euryodendron excelsum H. T. Chang(Chen et al 2020) and Argania spinosa (L.) Skeels(Amghar et al 2021).A number tissues can be involved in the formation of shoots, such as the pericycle, subepidermal cells, and epidermal cells, depending on the plant(Atta et al 2009;Wang et al 2015). This study suggested that the shoots of A. chinensis originated from cambium cells and that the shoots had obvious morphological characteristics at different development stages.…”
supporting
confidence: 93%
“…This indicates that in order to ensure a high survival rate and good growth status of the transplanted plants, the nutrition and air permeability of the transplant substrate are indispensable. The present result is in agreement with the previous ndings observed in Euryodendron excelsum H. T. Chang(Chen et al 2020) and Argania spinosa (L.) Skeels(Amghar et al 2021).A number tissues can be involved in the formation of shoots, such as the pericycle, subepidermal cells, and epidermal cells, depending on the plant(Atta et al 2009;Wang et al 2015). This study suggested that the shoots of A. chinensis originated from cambium cells and that the shoots had obvious morphological characteristics at different development stages.…”
supporting
confidence: 93%
“…The root system extends deep into the soil already in the first phases of the tree growth, making transplanting difficult and rarely successful (Lybbert et al 2004). Further, mass propagation of argan cuttings is limited due to fungi diseases (Bakry et al 2009) and to difficulties related to rooting and survival during transplantation in the field (Amghar et al 2021;Bousselmame et al 2001;Benbya et al 2019). In addition, seed propagation is challenging also due to heterogeneity in seed size, viability and dormancy, which are strongly genotype-dependent (Justamante et al 2017).…”
Section: Difficulties In Propagation and Germinationmentioning
confidence: 99%
“…The appropriate medium state for adventitious rooting depends on the plant genotype. Most previous research on adventitious root induction was conducted with gelled medium, such as the adventitious root induction of Argania spinosa and Morinda citrifolia from shoots and leaf explant, respectively [ 39 , 40 ], because the solidified medium provides a supporting material and acts as a pH stabilizer [ 41 ]. Our results also showed denser lateral roots and root hairs on adventitious roots in the semisolid medium.…”
Section: Resultsmentioning
confidence: 99%